2004
DOI: 10.1111/j.1747-4469.2004.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Social License and Environmental Protection: Why Businesses Go Beyond Compliance

Abstract: This article examines the concept of the corporate “social license,” which governs the extent to which a corporation is constrained to meet societal expectations and avoid activities that societies (or influential elements within them) deem unacceptable, whether or not those expectations are embodied in law. It examines the social license empirically, as it relates to one social problem–environmental protection–and as it relates to one particular industry: pulp and paper manufacturing. It shows try the social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
232
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(243 citation statements)
references
References 21 publications
1
232
0
10
Order By: Relevance
“…Voluntary actions and incentives are approaches that have been widely used and can be effective in reducing environmental impacts (Dietz & Stern, 2002; Gunningham, Kagan & Thornton, 2004; Stafford, 2012). However, in regard to the conservation issue of vessel strikes of large whales, mandatory and enforced changes in vessel operations appear to have considerable conservation value while adherence to—and therefore effectiveness of—previously implemented voluntary measures to reduce whale disturbance (Wiley et al, 2008) and vessel/whale collisions (Silber, Adams & Bettridge, 2012) was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voluntary actions and incentives are approaches that have been widely used and can be effective in reducing environmental impacts (Dietz & Stern, 2002; Gunningham, Kagan & Thornton, 2004; Stafford, 2012). However, in regard to the conservation issue of vessel strikes of large whales, mandatory and enforced changes in vessel operations appear to have considerable conservation value while adherence to—and therefore effectiveness of—previously implemented voluntary measures to reduce whale disturbance (Wiley et al, 2008) and vessel/whale collisions (Silber, Adams & Bettridge, 2012) was low.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many regulatory settings, limited resources may restrict enforcement actions and assessments of compliance to infrequent inspections (e.g., site visits), surveys, interviews, or self-reporting (Winter & May, 2001; Gunningham, Kagan & Thornton, 2004; Gray & Shimshack, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Still, it is likely that the reputation liability effect is dependent on company size (Gunningham et al, 2004). Previous research has shown that SMEs are heterogeneous in nature (Brammer et al, 2012).…”
Section: Csr and Monitoring (H1)mentioning
confidence: 99%
“…However, to operate effectively within a community and to expand, an industry requires a social licence to operate, going beyond what is just required for strict compliance with the regulation or law (Gunningham et al 2004). One of the barriers to the development of aquaculture in Europe is limited access to new sites.…”
Section: Increased Social Licencementioning
confidence: 99%